Factors associated with insulin-like growth factor-1 in children with thalassemia major - Muhammad Riza; Sri Mulatsih; Rina Triasih (Indonesian Pediatric Society, 2019)
Background Insulin-like growth factor-1 (IGF-1) deficiency is the major cause of growth disorders and delayed puberty in children with thalassemia. Hence, identifying factors contributing to IGF-1 deficiency in thalassemia is of importance. Objectives To evaluate the correlation between IGF-1 level and nutritional status, ferritin level, pre-transfusion hemoglobin, thyroid, as well as alanine transaminase level. Methods We conducted a study in children aged 2 to 18 years with thalassemia major who visited outpatient clinics at two hospitals in Indonesia, Dr. Sardjito Hospital, Yogyakarta and Dr. Moewardi Hospital, Surakarta, Central Java, from July to December 2015. Clinical, laboratory, and demographic data were reviewed from medical records. IGF-1 levels were measured using an immunochemiluminiscent method. Results A total of 48 children were recruited into the study. Subjects mean IGF-1 level was 109.28 ng/mL (SD 90.26) ng/mL. Seventy-five percent of the children had IGF-1 level < -2SD. Subjects mean ferritin, pre-transfusion hemoglobin and ALT levels were 3.568 (SD 2131.31) ng/mL; 7.97 (SD 0.85) g/dL and 49.7 (SD 43.1), respectively. Most of the children (91.7%) was eutyroid, with a mean of TSH and FT4 level was 2.7 (SD 1.5) nmol/L and 12.3 (SD 7.1) Î¼IU/ml, respectively. Ferritin level had no significant correlation with IGF-1 level (r=-0.794; P=0.431). However, a strong, positive correlation was documented between pre-transfusion hemoglobin level and IGF-1 level (r=2.380; P=0.022). Multivariate linear regression analysis revealed that factors with significant correlations to IGF-1 level were pre-transfusion hemoglobin level <8 g/dL (Î²=-0.090; 95%CI -0.002 to 0.182; P=0.056) and undernutrition (Î²=0.077; 95%CI 0.045 to 0.109; P<0.001). Conclusion Low pre-transfusion hemoglobin level and undernutrition are significantly correlated to low IGF-1 level in children with thalassemia major.